Long-term Risk of Colorectal Cancer After Removal of Conventional Adenomas and Serrated Polyps - He, Xiaosheng; Hang, Dong; Wu, Kana; Nayor, Jennifer; Drew, David A; Giovannucci, Edward L; Ogino, Shuji; Chan, Andrew T; Song, Mingyang (Gastroenterology (New York, N.Y. 1943), 2020)
Endoscopic screening reduces incidence and mortality of colorectal cancer (CRC) because precursor lesions, such as conventional adenomas or serrated polyps, are removed. Individuals with polypectomies are advised to undergo colonoscopy surveillance to prevent CRC. However, guidelines for surveillance intervals after diagnosis of a precursor lesion, particularly for individuals with serrated polyps, vary widely, and lack sufficient supporting evidence. Consequently, some high-risk patients do not receive enough surveillance and lower-risk subjects receive excessive surveillance. We examined the association between findings from first endoscopy and CRC risk among 122,899 participants who underwent flexible sigmoidoscopy or colonoscopy in the Nurses' Health Study 1 (1990-2012), Nurses' Health Study 2 (1989-2013), or the Health Professionals Follow-up Study (1990-2012). Endoscopic findings were categorized as no polyp, conventional adenoma, or serrated polyp (hyperplastic polyp, traditional serrated adenoma, or sessile serrated adenoma, with or without cytological dysplasia). Conventional adenomas were classified as advanced (≥10 mm, high-grade dysplasia, or tubulovillous or villous histology) or nonadvanced, and serrated polyps were assigned to categories of large (≥10 mm) or small (<10 mm). We used a Cox proportional hazards regression model to calculate the hazard ratios (HRs) of CRC incidence, after adjusting for various potential risk factors. After a median follow-up period of 10 years, we documented 491 incident cases of CRC: 51 occurred in 6161 participants with conventional adenomas, 24 in 5918 participants with serrated polyps, and 427 in 112,107 participants with no polyp. Compared with participants with no polyp detected during initial endoscopy, the multivariable HR for incident CRC in individuals with an advanced adenoma was 4.07 (95% confidence interval [CI] 2.89-5.72) and the HR for CRC in individuals with a large serrated polyp was 3.35 (95% CI 1.37-8.15). In contrast, there was no significant increase in risk of CRC in patients with nonadvanced adenomas (HR 1.21; 95% CI 0.68-2.16, P = .52) or small serrated polyps (HR 1.25; 95% CI 0.76-2.08; P = .38). These findings provide support for guidelines that recommend repeat lower endoscopy within 3 years of a diagnosis of advanced adenoma and large serrated polyps. In contrast, patients with nonadvanced adenoma or small serrated polyps may not require more intensive surveillance than patients without polyps.